2023
DOI: 10.3390/ijfs11010031
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Banks’ Stock Market Prices during Long-Term Crises

Abstract: Countries are drastically impacted by financial and fiscal crises. Financial crises have the worst impact on not only society, but also the economy. The Canadian economy underwent financial crises and recessions several times during the last century. In this paper, daily closing stock prices of five large Canadian banks were studied during the last five crisis periods. It is aimed to determine the most effective or dominant index prices on the daily closing stock price of the banks during the crisis periods. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The study employs multiple regression analysis to explore the relationship between the stock prices of banks and the selected macroeconomic indicators, as it has been proven quantitative technique for the same in a few prior studies [13][14][15][16][17]. The regression model is specified as follows:…”
Section: Discussionmentioning
confidence: 99%
“…The study employs multiple regression analysis to explore the relationship between the stock prices of banks and the selected macroeconomic indicators, as it has been proven quantitative technique for the same in a few prior studies [13][14][15][16][17]. The regression model is specified as follows:…”
Section: Discussionmentioning
confidence: 99%
“…Castanias [12] examined variability in stock market prices, challenging the assumption that price changes are drawn from a stationary distribution and suggesting that the arrival rate of broad economic information influences this variability. Ruzgar et al [13] analyzed Canadian banks' stock prices during financial crises, finding that certain indexes positively influenced bank stocks during these times. Ibrahim [14] explored how stock market returns can predict actual output in Malaysia and found that stock returns have a predictive power for the economy's output in short forecasting periods.…”
Section: General Studies On the Stock Marketmentioning
confidence: 99%